(untitled) (Polish Yearbook of International Law, 2018)
This article explores investment protection under Chinese international investment agreements (IIAs), particularly under the China-Poland bilateral investment treaty (BIT). As a state that both imports and exports foreign direct investment, China currently promotes balanced and safeguarded BITs that protect its increasing overseas investments and preserves the necessary space to regulate in the public interest. The Chinese government remains reluctant to be directly involved in investment arbitration as a respondent, while Chinese investors are active in taking advantage of the IIAs’ regime. When compared to China’s recent treaty practice and new developments in global investment governance, the China-Poland BIT is relatively outdated in terms of investment protection, promotion, social clauses, and dispute settlement. In terms of the investment protection effects of BITs, China is seemingly in a more urgent position to update the China-Poland BIT. However, if we evaluate the overall effects of a modernized BIT on investment promotion, regulation, and dispute settlement, an updated China-Poland BIT will fit the interests of both the Polish and Chinese governments. Notwithstanding the on-going negotiation between the EU and China, this article aims, along with presenting the Chinese practice regarding BITs, to describe de lege lata the state of protection offered to Chinese and Polish investors under the China-Poland BIT.